2001
DOI: 10.1007/bf02234593
|View full text |Cite
|
Sign up to set email alerts
|

Complications of dynamic graciloplasty

Abstract: Severe complications occur frequently after dynamic graciloplasty, but are usually treatable. They often require one or more reoperations and can lead to significant delays in completion of therapy. In most cases therapy can be salvaged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
6

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(17 citation statements)
references
References 10 publications
2
9
0
6
Order By: Relevance
“…A graciloplastia dinâmica tem demonstrado taxa de sucesso inferior a 45% em dois anos, com uma maior taxa de sucesso no primeiro ano. Além disso, as taxas de complicações nestes estudos giraram em torno de 40%, muitas delas de tratamento cirúrgico 49,50 .…”
Section: • Graciloplastiaunclassified
“…A graciloplastia dinâmica tem demonstrado taxa de sucesso inferior a 45% em dois anos, com uma maior taxa de sucesso no primeiro ano. Além disso, as taxas de complicações nestes estudos giraram em torno de 40%, muitas delas de tratamento cirúrgico 49,50 .…”
Section: • Graciloplastiaunclassified
“…This part of the procedure may be performed at the same time as the graciloplasty (single stage procedure) or as a separate procedure approximately six weeks later (two-stage procedure). Matzel et al found no difference in the complication rate between the single- and two-staged procedures [40]. To prevent seroma formation, the leg should be bandaged.…”
Section: Graciloplastymentioning
confidence: 99%
“…A graciloplastia dinâmica tem demonstrado taxa de sucesso variável em torno de 60 a 80% no tratamento da incontinência fecal em algumas séries limitadas de pacientes [73][74][75][76][77] . No entanto, estudos mais recentes, inclusive um estudo prospectivo multicêntrico de Metzel et al 79 , demonstram taxas de sucesso não superiores a 45% em dois anos, com maior taxa de sucesso no primeiro ano 78,79 . Além disso, a taxa de complicações importantes nestes estudos giraram em torno de 40%, muitas delas de tratamento cirúrgico.…”
Section: Graciloplastiaunclassified